The Service Sector as India’s Road to Economic Growth : An Analysis - Hada, Dr. Bhupendra Singh; Suri, Ashish Suri (Journal of Contemporary Research in Management (JCRM), 2019)
Services are tasks or functions, which are performed by a group or an individual, for which price is decided on the basis of demand if that particular service is available in the related market. Services are sometimes referred to as intangible goods. The consumption is done only at the point of production. Services are typically non-transferable that means they cannot be resold or purchased at a different price. In an economy the service sector perform a vital role in the resource allocation process. The service industry is not only the World’s largest industry, but also contributes major portion in GDP. It generates three times more employment in comparison tothe manufacturing sector. The contribution of the service industry to the GDP of countries like India is over 56.1% in 2015-16. The service sector is not only the star performer in terms of employment generation, but has also attracted significant export growth, foreign direct investment flow, employment generation and portrayed itself for sustainable economic development. As per the report of Department of Industrial Policy and Promotion (DIPP) India’s service sector has shown a remarkable presence to attract the maximum amount of FDI equity inflow during the period of April 2000 -December 2016, amounting to about US$ 58.34 billion, which is about 18% of the total foreign inflow. In addition to this more than 50% of total export of services comes from export of software services in India. On the basis of this rapid growth in service sector growth rate will going to be more than 60 percent in the next fifteen years in India. After China, India has got the second position as the fastest growing service providing country in the world. The present study is all about the analysis of the potential and capability of the service sector in the economic growth of the country over the last couple of decades. The main objective of this study is to see the correlation between the growth in the Indian service sector along with growth in the economy in terms of growth in GDP, per capita income and foreign investment.